Estimation of nitrogen load in Vietnam using native administrative data - Vu Thanh, L.A.(Shinshu Univ., Matsumoto, Nagano (Japan). Faculty of Science); Toda, H (Journal of the Japanese Agricultural Systems Society, 2005)
The development of agriculture as well as the growth of population in Vietnam in the last 40 years has caused serious environmental problems such as contamination of ground water with nitrate, and eutrophication of lakes and reservoirs. Although those environmental problems have been recognized, only a few quantitative evaluations of the nitrogen loading have been conducted on a countrywide scale. This paper presents the countrywide estimation of N loads generated from various sources such as agriculture, livestock waste, human waste, and forest in Vietnam by using the native statistical data in addition to the FAO database from 1961 to 2001. N loads were calculated by the difference between input and output of N in each compartment. N loads in 2010 were also calculated using the data provided by the Ministry of Agriculture and Rural Development in Vietnam. Total N load increased 7 times from 171 x 10(3) to 1,191 x 10(3) ton y(-1) during the last 40 years. The increase in N load from agricultural area (upland and paddy fields) was prominent (851 x 10(3) ton in 2001), reflecting the marked increase of chemical fertilizer use. N load derived from humans waste increased 3-fold from 85 x 10(3) to 265 x 10(3) ton y(-1), and that of livestock waste increased about 5-fold from 30 x 10(3) to 145 x 10(3) ton y(-1). N load from forest remained small (71 x 10(3) ton in 2001). Large N load were observed in intensive agricultural areas such as the Red River Delta and the Mekong River Delta. Further noticeable increase in N loads from agricultural area and livestock waste was predicted in the next 10 years, and the total N load might reach 1,790 x 10(3) ton y(-1) in 2010. Serious nitrate pollution will occur in the both deltas, but N loads in the other rural regions might remain low level due to their low population density and stagnant activity in agriculture.